Online Extremism : Agents of Disruption in the Digital Age - Jerard, Jolene (2019)
Online extremism is a fast-growing threat that disrupts and threatens to damage the social fabric of diverse communities. The extremists’ exploitation of communication technologies to radicalise and incite violence presents a grave challenge to racial and religious harmony that will need to be addressed.